Trends in Library Expenditure of Top Indian Colleges in Recent Years: A Statistical Analysis - Adhikary, Biswajit (Journal of Information and Knowledge, 2025)
It is said that library is the central organ of any educational institute. However, the prominence is not visible from the financial allocation for academic libraries in India. In recent years, due to assessments, accreditation issues, rankings, etc., colleges and universities have been forced to allocate a certain percentage of their annual budget for the library. This process has brought some standardisation and consistency in the budgetary allocation for academic libraries. In this study, the top 100 colleges according to the NIRF ranking 2023 were considered, focusing on the trends in library expenditures. The study compares the trend in library expenditure of different kinds of colleges classified according to certain criteria. It also tries to assess the impacts of library expenditure on the NIRF rankings. The analysis shows that the average per capita library expenditure of the top 100 Indian colleges is ₹370.52, while the figure is ₹519.75 in the case of the top 25 colleges. The study also reveals that the library expenditure has a negligible impact on the NIRF score. The findings of this paper indicate some benchmarks for the colleges willing to have better grades or rank in future.